Writing to learn: Can reflection journals be used to promote self-reflection and learning? - LEW, Duan Ning, Magdeleine (Institutional Knowledge at Singapore Management University, 2011)
The purpose of the present study was to evaluate whether there is evidence of reflection in student-written journals and to investigate whether students show improvements in their reflective skills through journal keeping. To that end, the reflection journals of 3460 first-year students enrolled in a polytechnic were studied by means of an automated coding procedure. Data used in the analyses were students' journals for an entire week, collected once at the beginning and again at the end of an academic year. Outcomes of the content analyses suggest that there is evidence of reflection in students' journals and that students reflected on three general categories related to their learning: critical review of past learning experiences, cognitive learning strategies and summaries of what was learnt. Furthermore, the findings also indicate that students show improvements in their reflective skills as they progressed through the academic year. The findings when taken together suggest that reflection journals can be used to promote self-reflection and learning amongst students.